Pendampingan Aplikasi Pupuk Hayati pada Kelompok Tani Subur Selaras Alam - Ali Ikhwan; Dian Indratmi (Universitas Tribhuwana Tunggadewi Malang, 2019)
The Subur Selaras Alam farmer group is a group of vegetable farmers with an average land area of around 0.25 Ha. This farmer group has concerns over the decreasing land conditions due to excessive pesticide residue contamination and excessive chemical fertilization. In an effort to increase soil fertility and the quality of vegetables that are safer and healthier for consumers, farmer groups face several problems regarding biofertilizer technology. Among them are (1) partners have not mastered the technology of production and application of biofertilizers in the field, and (2) partners have not mastered organic farming cultivation management. Methods for overcoming partner problems are carried out with Focus Group Discussion (FGD), training and assistance in the application of biofertilizer technology in the field. The results of the dissemination of technology in the field that were obtained: (1) farmer group